Immunotherapeutic applications of IL-15. (September 2012) - Croce, Michela; Orengo, Anna Maria; Azzarone, Bruno; Ferrini, Silvano
IL-15 is a member of the IL-2 family of cytokines, which play a fundamental role in innate and adaptive immune responses. IL-15 has pleiotropic immune-enhancing activities, as it stimulates NK, T and NKT cell proliferation, survival and effector functions. In view of these properties, IL-15 is regarded as a good candidate for cancer immunotherapy. This possibility is reinforced by its low toxicity and efficacy in preclinical tumor models. The use of IL-15 to boost the immune response in HIV infection has also been proposed, although further studies are required to establish potential risks and benefits. Clinical trials of IL-15 have been initiated in cancer patients and in HIV vaccination and will elucidate the potential of IL-15-based immunotherapy. The purpose of this review is to provide an update on the potential applications of IL-15 in cancer immunotherapy and HIV infection.